Leverage ratio requirement and credit allocation and bank stability - Ilkka Kiema; Esa Jokivuolle (Bank of Finland, 2011)
We study the effects on credit allocation and bank stability of introducing a leverage ratio requirement (LRR) on top of risk-based capital requirements, as in Basel III. For the current 3% LRR, both low-risk and high-risk loan rates and volumes remain essentially unchanged, because banks previously specializing in low-risk lending can adapt by granting both low-risk and high-risk loans. For sufficiently high LRRs, low-risk lending rates would significantly increase and high-risk lending rates would fall. In the presence of severe model risk concerning low-risk loans, as happened in the subprime crisis, the current 3% LRR might even reduce bank stability, counter to regulatory intentions. This is because the allocational effect caused by the LRR, which makes bank loan portfolios more alike, may turn beneficial risk spreading into harmful risk contamination. For higher levels of LRR, however, bank stability is likely to be improved even in the presence of model risk.
URN:NBN:fi:bof-20140807427
Keywords: D41; D82; G14; G21; G28; 330; bank regulation; Basel III; capital requirements; credit risk; leverage ratio